The Influence of Flipped Classroom Learning Model Application on Problem Solving Ability and Learning Motivation - Faridah, Nilen; Ridlo, Saiful; Saptono, Sigit (Universitas Negeri Semarang, 2021)
One of the 21st century skills that students need to be able to compete in the international world is Thingking. Thingking is the ability to solve problems, this aspect is an important skill because a person's success is determined by his thinking skills, especially in solving a problem. In addition to problem-solving abilities, research also examines aspects related to learning motivation. One solution to improve problem-solving skills and learning motivation is by learning flipped classroom. Type of experimental research. The population in this study were students of class X SMK Pharmasi Semarang. Data collectors used prettest and posttest to determine the value of problem solving abilities and the value of a questionnaire to determine students' learning motivation. The results: (1) there is an effect of the application of the flipped classroom learning model on the problem solving ability of students with> 75% and it meets the minimum completeness criteria, Based on the Independent Sample T-test with the SPSS 25 program, significant results are obtained 2) there is an effect of application Learning model of flipped classroom on students' motivation. The conclusion is that there is an effect of the application of the flipped classroom learning model on problem solving abilities and learning motivation of students.